Modelling the long throw in soccer using aerodynamic drag and lift - Bray, K.; Kerwin, D. G. (The Engineering of Sport 5, Volume 1, 2004)
Research interests include all those aspects of ball games that can be represented by mathematical models although current interest centres on the biomechanics of soccer, specifically the modelling of the flight of a soccer ball in a direct free kick. Coaches and players alike are aware of the goal-scoring potential of this important set play. In the 1998 World Cup, for example, of the 171 goals scored, 50% originated from set plays of all kinds and 50% of these in turn were from free kicks. Biomechanical treatments of kicking have tended to concentrate on instep kicking and have looked almost exclusively at maximal ball velocity as the key output. This is not the most important ingredient in beating a defensive wall, however, as elite players use a combination of speed and spin to swerve the ball over or around the defensive wall.